Intravagal parathyroid adenomas: Case report and literature review. Issue 7 (13th April 2020) - List, Marna A.; Boyce, Brian J.; Dziegielewski, Peter T.
Abstract: Intravagal parathyroid adenomas remain an exceedingly rare diagnosis; however, their true incidence may be higher than currently known. It is important to keep intravagal sites within the list of potential ectopic locations of parathyroid adenomas. Abstract : Intravagal parathyroid adenomas remain an exceedingly rare diagnosis; however, their true incidence may be higher than currently known. It is important to keep intravagal sites within the list of potential ectopic locations of parathyroid adenomas.